2004
DOI: 10.1046/j.0902-4441.2003.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and brain function following high‐dose recombinant human erythropoietin in low‐risk myelodysplastic syndromes: a preliminary report

Abstract: A high-dose induction phase with rHuEPO followed by maintenance therapy may be an effective therapeutic schedule for low-risk MDS patients. The erythroid response was associated with positive changes in the QOL. Neurophysiological improvements occurred only in a part (50%) of responding patients, mainly those who showed altered results at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Several studies have reported a positive correlation between Hb levels and HRQoL [9,19,20,[24][25][26][27][28][29][30][31], although this correlation is not consistent [6]. The current data reinforce the notion of a relationship between Hb levels and QOL-E© as specific patient-reported outcome in MDS patients.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have reported a positive correlation between Hb levels and HRQoL [9,19,20,[24][25][26][27][28][29][30][31], although this correlation is not consistent [6]. The current data reinforce the notion of a relationship between Hb levels and QOL-E© as specific patient-reported outcome in MDS patients.…”
Section: Discussionsupporting
confidence: 76%
“…However, patients who had erythroid responses endorsed significantly improved physical, emotional, and functional well-being plus improved fatigue and overall QOL, as previously reported. 8,9,[14][15][16] Thus, albeit this was a subset analysis, improving anemia appears to be an important intervention to maintain or improve QOL in patients with MDS.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Therapy with granulocytestimulating factor (G-CSF) synergizes with EPO and improve erythroid responses in a portion of MDS patients not responding to EPO alone. [10][11][12][13] Several studies demonstrated improvement in quality of life (QOL) in MDS patients responding to ESAs, 12,[14][15][16][17] whereas one study showed no such improvement. 13 Although therapy with ESAs in certain non-MDS cancer patients was associated with an increased risk of cardiovascular and thrombotic events and shortened survival, 18,19 nonrandomized trials with EPO treatment of MDS patients have not demonstrated such adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Patients not reaching an Hb of 120 g ⁄ L after 16 wk received, in addition to continued growth factor treatment, erythrocyte transfusions to maintain an Hb > 120 g ⁄ L for at least 8 wk (study weeks [18][19][20][21][22][23][24][25][26]. The rationale for maintaining growth factor therapy was to maintain the positive effects on haemoglobin levels of partial remissions and potential effects of subclinical responses.…”
Section: Targeted Transfusion Therapymentioning
confidence: 99%
“…Darbepoetin alfa (DA) has a threefold increased plasma half-life compared with earlier EPO compounds and has shown encouraging response rates as a single agent (9)(10)(11)(12)(13) and combined with G-CSF (14)(15)(16). The reduced quality of life (QoL) associated with MDS (6,17) may be improved by an erythropoietic response to growth factors according to some (18)(19)(20) but not other (21) studies.…”
mentioning
confidence: 99%